# What is the range of the function f(x) = 3x2 + 6x – 9

f(x)=3x^2-6x+1

My solution is:

The domain is all real numbers--there are no restrictions like a square root or variable in the denominator

this is a U shape parabola and you want to find the bottom point, it is at the vertex

x=-b/2a =- (-6) /2 (3) =1

f(1) =3(1)^2 -6(1) +1 =3-6+1 =-2

the minimum is (1, -2)

so the range is all real numbers >= -2

By examining my solution, you could just answer the problem on your own! I hope it helps!

## Related Questions

Which ordered pair is a solution of the equation 2x − y = 9 (-4,1) (-2,5) (5,1) (6,-3)

So based on my solution, the correct answer would be the third option: (5,1)

So let us try to plug in the values.

2(5) - 1 = 9

10 -1 = 9

9 = 9

So this is the correct one. Hope this answers your question.

Find the multiplicative inverse of 6 + 2i.

First thing to do is get rid of the i. Multiplying by 6 - 2i will do this

( 6 + 2i)(6 - 2i) = 6^2 - (2i)^2 = 36 - 4(-1) = 36 + 4 = 40

Dividing by 40 gets you 1

(6 + 2i) (6-2i)/40 = 1

**The answer is (6 - 2i)/40 = (3 - i)/20**

I hope my answer has come to your help. God bless and have a nice day ahead!

Solve the equation for y 2x+6y=13

2x+6y=13

Next, transfer 2x to the right side and it will look like this:

6y=13-2x

Now, divide both sides by 6, and it will look like this:

y=13-2x

--------

6

So, this is the final answer for y.

Hope this answers your question. Have a great day!

**Answer:**

D

**Step-by-step explanation:**

She showed that f(n) - f(n - 1) was a constant difference.

The definition of an arithmetic sequence is** the difference between consecutive terms is constant, aka common difference.**

solve for x :

−3(6−2x)≥4x+12

−18+6x≥4x+12

2x≥30

x≥15

**So the answer is D ) 15 to +infinity**

I hope my answer has come to your help. God bless and have a nice day ahead!

## Use our writing service to score better and meet your deadlines

No matter what kind of academic paper you need, it is simple and secure to hire a writer for a price you can afford at StudyHawks. Save more time for yourself.

How to solve this problem 14-6= 10-6=?

Algebraic terms are separated by ______. Choose all that apply. 1)= 2)+ 3)x 4)÷ 5)-

__Answer__

1)=

2)+

5)-

__Explanation__

When letter or numbers are separated by multiplication or division can be combined to make one term.

In an algebra equation, terms are separated by an addition sign, subtraction sign or an equal sign. For example,

3a + 7b = 21.

This equation have 3 terms.

**Answer:**

A) -4c^2 + 4c + 6

**Step-by-step explanation:**

The given polynomial is 2 + 7c – 4c^2 – 3c + 4

Add the like terms.

2 + 4 + 7c - 3c -4c^2

= 6 + 4c - 4c^2

Write it in a standard form

= -4c^2 + 4c + 6

Answer is A) -4c^2 + 4c + 6

Hope this will helpful.

Thank you.

(a−b)²+b²/a²

proof

if A is the area of the

inner squared, so A= c², and c²= (a−b)²+b²

so the side of the outer must be a-b +b=a, its area is a²

Unordered polynomial is

7x3y3 + 4 - 11x5y2 - 3x2y

Polynomial in descending order looks like this

-11x5y2 + 7x3y3 - 3x2y + 4

Degree of the second term is 5 ( because of x5 )

## Use our writing service to score better and meet your deadlines

No matter what kind of academic paper you need, it is simple and secure to hire a writer for a price you can afford at StudyHawks. Save more time for yourself.

Which of the following is a factor of 2x4 + 22x3 + 60x2? 2x3 x4 x + 4 x + 5

The correct answer is **Option D, **or **X+5**. I hope I answered this question to your satisfaction Have a nice day!

► For instance, the quadratic equation:

x² – (6 + 4i)x + (9 + 12i) = 0

has for discriminant:

Δ = (6 + 4i)² – 4(9 + 12i) = 36 – 16 + 48i – 36 – 48i = -16

which is indeed negative.

Its solutions will then be:

x₁ = [(6 + 4i) + 4i]/2 = 3 + 4i

x₂ = [(6 + 4i) – 4i]/2 = 3

And the other solution here is 3.

► If you are not convinced, the quadratic equation:

x² – (6 + 5i)x + (5 + 15i) = 0

has for discriminant:

Δ = (6 + 5i)² – 4(5 + 15i) = 36 – 25 + 60i – 20 – 60i = -9

which is indeed negative.

Its solutions will then be:

x₁ = [(6 + 5i) + 3i]/2 = 3 + 4i

x₂ = [(6 + 5i) – 3i]/2 = 3 + i

And the other solution here is 3+i.

► In fact, every quadratic equation of the form:

x² – [6 + (4 + α)i]x + (3 + 4i)(3 + αi) = 0

where α is any real, has for discriminant:

Δ = [6 + (4 + α)i]² – 4(3 + 4i)(3 + αi)

= 36 – (4 + α)² + 12(4 + α)i – 36 + 16α – 12(4 + α)i

= 16α – (4 + α)²

= 16α – 16 – 8α – α²

= -16 + 8α – α²

= -(α – 4)²

WILL be negative.

Their solutions will then be:

x₁ = [ [6 + (4 + α)i] – (α – 4)i ]/2 = 3 + 4i

x₂ = [ [6 + (4 + α)i] + (α – 4)i ]/2 = 3 + αi

And the other solution will then be is 3+αi.

Since α can take any real value, you'll obtain an infinity of solutions of the form 3+αi.

► So conclusively:

If the discriminant of a quadratic is negative AND one of the solutions is 3+4i, the only thing we can say about the other solution is that its real part must be 3.

**If ST = 21, SP = 3b – 11, and PT = b + 4, the value of b would be 14.**

I hope my answer has come to your help. God bless and have a nice day ahead!

First one looks like you are squaring the number, then multiplying the result by 4, i.e.

y=4x2

second one is similar, but instead of squaring and multiplying by 4, you are squaring and then dividing by 2

I hope my answer has come to your help. God bless and have a nice day ahead!

is as follows

mean=13(.5)=6.5

variance=6.5(.5)=3.25

Pr[fewer than 4]=

Pr[N<=3] Apply the continuity correction

Pr[N<=3.5]~=Pr[Z<3.5-6.5/sqrt(3.25)]=

Pr[Z<-1.66]=0.048457226

I hope my answer has come to your help. God bless and have a nice day ahead!

## Use our writing service to score better and meet your deadlines

No matter what kind of academic paper you need, it is simple and secure to hire a writer for a price you can afford at StudyHawks. Save more time for yourself.

A = (x+3)^2 = x^2+6x+9

Because for so solving the additive inverse of 9xy² + 6x²y - 5x³

-1(9xy² + 6x²y - 5x³) then it will turn to this ⇒ (-1)(9xy²) + (-1)(6x²y) + (-1)(-5x³)

**-9xy² - 6x²y + 5x³**is the additive inverse of the given polynomial.

6 times the square root of 2.25 and then minis 4.23 =

________________

6√(2.25) - 4.23 = ?

__________________

6√(2.25) - 4.23 =

______________________

6*(1.5) - 4.23 =

_______________

9 - 4.23 =

_______________

4.77

Now we'll plug in the numbers they give us into the formula:

y-4= 0(x+2).

## Use our writing service to score better and meet your deadlines

Solve the inequality. y – 5 ≥ 11

Add 5 to the both sides,

y - 5 + 5 ≥ 11 + 5

**y ≥ 16**

Hope this helps!

Solve the inequality. p – 9 < –9

p-9 < -9

p-9+9 < -9+9

p <0

Solve the inequality by adding. x – 7 > –11

x-7+7> -11+7

x> -4

**1) The answer is: [B]: r = 5 .**

**__________________________**

**Explanation:**

**___________**_______________

Given: 7r − 7 = 2r + 18 ; Round your answer to the nearest tenth, if necessary.

____________________________

Since "r" is the only variable given, let us assume we want to solve for "r" (instead of "x").

___________________________

→ Subtract "2r" from EACH SIDE of the equation; and & add "7" to EACH SIDE of the equation:

_____________

→ 7r − 7 − 2r + 7 = 2r + 18 − 2r + 7 ; to get: → 5r = 25 ;

_____________

→ Now, divide EACH SIDE of the equation by "5"; to isolate "r" on one side of the equation; and to solve for "r" :

______________

→ 5r / 5 = 25 / 5 → r = 5 → which is: "Answer choice: [B]".

_________________

**Let us check our answer, by plugging in "5" for "r" in the original equation:**

_________________

→ 7r − 7 = 2r + 18 ; → 7(5) − 7 =? 2(5) + 18? ;

______________________

→ 35 − 7 =? 10 + 18 ?; → 28 =? 28? Yes!

______________________

**2) The answer is: [D]: x = 2 .**

**_____________**

**Explanation:**

_____________

Given: 2x + 12 = 18 − x ; Solve for "x" (round to nearest tenth, if necessary).

_______________

→ Add "x" to EACH SIDE of the equation, & subtract "12" from EACH SIDE of the equation: → 2x + 12 + x − 12 = 18 − x + x − 12 ;

______________

→ To get: 3x = 6 ; → Divide EACH SIDE of the equation by "3";

to isolate "x" on one side of the equation; and to solve for "x":

_____________

→ 3x / 3 = 6 / 3 ; → x = 2 ; which is: "Answer choice: [D]".

______________

**Let us check our answer, by plugging in "2" for "x" in the original equation:**

________________

→ 2x + 12 = 18 − x ; → 2(2) + 12 =? 18 − 2 ?

________________

→ 4 + 12 =? 18 − 2 ? ; → 16 =? 16? Yes!

________________________________

**3) The answer is: [A]: x = -3 .**

**_____________**

**Explanation:**

________________

Given: 8x − 3 = 15x + 18 ; Solve for "x". Round your answer to the nearest tenth, if necessary.

_________________

→ Subtract "8x" from EACH SIDE of the equation, & add "3" to EACH SIDE of the equation:

_______________

→ 8x − 3 − 8x + 3 = 15x + 18 − 8x + 3 ; to get:

_______________

→ 0 = 7x + 21 ; → Subtract "21" from EACH SIDE of the equation;

_______________

→ 0 − 21 = 7x + 21 − 21 ; to get:

_______________

→ -21 = 7x ; Now divide EACH SIDE of the equation by "7";

to isolate "x" on one side of the equation; & to solve for "x":

_______________

→ = -21 / 7 = 7x / 7 ; → -3 = x ; which is "Answer choice: [A]."

**_________________**

**Let us check our answer, by plugging in "-3" for "x" in the original equation:**

________________

→ 8x − 3 = 15x + 18 ; → 8(-3) − 3 =? 15(-3) + 18 ?;

________________________

→ -24 − 3 =? -45 + 18 ? ; → -27 =? -27? Yes!

**___________________________**

**4) The answer is: [C]: y = 11 .**

**_____________**

**Explanation:**

**____________**

Given: 6y − 6 = 4y + 16 ; Solve for "y"; Round to the nearest tenth, if necessary.

____________

(Note: Since "y" is the only variable given; assume we are to solve for "y" instead of "x").

____________

→ Subtract "4y" from EACH SIDE of the equation, & add "6" to EACH SIDE of the equation; → 6y − 6 − 4y + 6 = 4y + 16 − 4y + 6 ; to get:

_______________

→ 2y = 22 ; Now, divide EACH SIDE of the equation by "2"; to isolate "y" one side of the equation; and to solve for "y" ;

_______________

→ 2y / 2 = 22 / 2 ; → y = 11 → which is "Answer choice: [C]".

**_______________________________**

**Let us check our answer, by plugging in "11" for "y" in the original equation:**

**___________________**

→ 6y − 6 = 4y + 16 ; → 6(11) − 6 =? 4(11) + 16 ?

_______________________

→ 66 − 6 =? 44 + 16 ? → 60 =? 60 ? Yes!

**__________________**

**5) The answer is: [B]: x = -11 .**

**_____________________**

**Explanation:**

**_________________**

Given: 3(x − 4) = 5(x + 2) ; Solve for "x". Round to the nearest tenth, if necessary.

**___________**

**→Note the "distributive property of multiplication":**

**_____________**

**a*(b + c) = ab + ac ; and: a*(b − c) = ab − ac ;**

**_______________**

→ Let us expand EACH SIDE of our given equation.

→Start with the "left-hand side":

____________

3(x − 4) = (3*x) − (3*4) = 3x − 12;

______________________________

→Now let us expand the "right-hand side" of the given equation:

____________

→ 5(x + 2) = (5*x) + (5*2) = 5x + 10 ;

______________

→Now, we can rewrite the original equation:

_______________

→ 3(x − 4) = 5(x + 2) ; by substituting the expanded values for EACH SIDE of the question: → 3x − 12 = 5x + 10 ;

__________________

→ Subtract "3x" from EACH SIDE of the equation; and add "12" to EACH SIDE of the equation: → 3x − 12 − 3x + 12 = 5x + 10 − 3x + 12 ; to get:

________________

→ 0 = 2x + 22; → Now subtract "22" from EACH SIDE of the equation:

______________

→ 0 − 22 = 2x + 22 − 22 ; to get: → -22 = 2x ;

__________

→ Divide EACH SIDE of the equation by "2"; to isolate "x" on one side of the equation; & to solve for "x" ;

_____________

→ -22 / 2 = 2x /2 ; → -11 = x ; which is "Answer choice: [B]".

______________

**Let us check our answer, by plugging in "-11" for "x" in the original equation:**

**___________**

→ 3(x − 4) = 5(x + 2) ; → 3(-11 − 4) =? 5(-11 + 2) ? ;

_______________________

→3(-15) =? 5(-9) ? ; → -45 =? -45 ? Yes!

**_____________________________________________**

**Hope these answers and explanations are helpful. Best of luck!**

## Use our writing service to score better and meet your deadlines

Solve for w. 2w=12-4w Simplify your answer as much as possible.

2w=12-4w

Firstly, let's simplify, and divide all terms by 2:

w=6-2w

Now, we add 2w over to the other side:

3w=6

And finally, we divide both sides by 3:

w=2

Hope this helps!

f ( x ) = √( 1 - x²), g ( x ) = - 2

= - 50/3

My = p ∫ x * ( f ( x ) ) dx

My = p ∫ x ( √(1+x²)) dx

Substitution: 1 - x² = u, x dx = - du/2

**M x = - 50/3, M y = 0**

M ≈ 5 * 6.3 ≈ 31.2

x = M y / M = 0 / 31.5 = 0

y = M x / M = -50/3 : 31.5 ≈ - 0.529

The center of mass is

**( 0, -0.529 )**

we have

Combine like terms

therefore

__the answer is the option C__

He combined the terms and incorrectly